Global Mindset and Entry Mode Decisions: The Moderating Roles of Managers’ Decision-Making Style and Managerial Experience - Jiang, Fuming; Ananthram, Subra; Li, Forest (Gabler Verlag, 2018)
From the managerial cognition perspective, we develop a contingency framework that empirically examines the effect of senior managers’ global mindset on their decisions regarding the choice of entry mode for foreign subsidiaries and how their cognitive decision-making style and managerial experience interact with their global mindset and thereby affect their decisions. Data were collected from both headquarters and subsidiary senior managers of 345 Chinese multinational enterprises. The results show that senior managers who exhibit a stronger global mindset tend to choose a lower-level ownership entry mode for their foreign subsidiaries. This tendency is stronger when senior managers possess a ‘thinking’ decision-making style as opposed to a ‘feeling’ decision-making style but weaker when senior managers have more experience in their managerial positions.